Linkages between Quaternary climate change and sedimentary processes in Hala Lake, northern Tibetan Plateau, China. (1st August 2015) - Wang, Rong; Zhang, Yongzhan; Wünnemann, Bernd; Biskaborn, Boris K.; Yin, He; Xia, Fei; Zhou, Lianfu; Diekmann, Bernhard
Highlights: End-member modeling of the grain size distribution in Hala Lake allowed the discrimination between lacustrine, eolian and fluvial sediments. Dominant clay sedimentation (slack water type) during the global Last Glacial Maximum (LGM) reflects ice interceptions in long cold periods. Eolian input is attributed to abrupt cold events (Heinrich Event I, Younger Dryas, 8.2 ka event). Transportation and depositional processes are affected by the extratropical Westwind system. Abstract: Profundal lake sediment cores are often interpreted in line with diverse and detailed sedimentological processes to infer paleoenvironmental conditions. The effects of frozen lake surfaces on terrigenous sediment deposition and how climate changes on the Tibetan Plateau are reflected in these lakes, however, is seldom discussed. A lake sediment core from Hala Lake (590 km 2 ), northeastern Tibetan Plateau spanning the time interval from the Last Glacial Maximum to the present was investigated using high-resolution grain-size composition of lacustrine deposits. Seismic analysis along a north–south profile across the lake was used to infer the sedimentary setting within the lake basin. Periods of freezing and melting processes on the lake surface were identified by MODIS (MOD10A1) satellite data. End-member modeling of the grain size distribution allowed the discrimination between lacustrine, eolian and fluvial sediments. The dominant clay sedimentation (slack water type) during the global Last Glacial Maximum (LGM) reflects ice interceptions in long cold periods, in contrast to abundant eolian input during abrupt cold events. Therefore, fluvial and slack water sedimentation processes can indicate changes in the local paleoclimate during periods of the lake being frozen, when eolian input was minor. Inferred warm (i.e., ∼22.7 and 19.5 cal. ka BP) and cold (i.e., ∼11–9 and 3–1.5 cal. ka BP) spells have significant environmental impacts, not only in the regional realm, but they are also coherent with global-scale climate events. The eolian input generally follows the trend of the mid-latitude westerly wind dynamics in winter, contributing medium-sized sand to the lake center, deposited within the ice cover during icing and melting phases. Enhanced input was dominant during the Younger Dryas, Heinrich Event 1 and at around 8.2 ka, equivalent to the well-known events of the North Atlantic realm.